Editorial: FEAST of biosensors: food, environmental, and agricultural sensing techniques - Mao, Kang; Zhang, Hua; Yang, Zhugen (Frontiers, 2024)
Biosensors are analytical devices that involve biological elements, such as nucleic acids, antibodies, enzymes, cells and microorganisms with a physicochemical (such as optical, electrical and mechanical) detectors. In the last 5 years the number of publications with the keyword “biosensor” is over 5,000 per year from the Web of Science and various biosensors are being designed and fabricated for high-efficiency, multiplex-functionality and high-flexibility sensing applications in the field of food, environment and agriculture. Many existing biosensors have the inherent capacity to achieve such goals; however, they require further development into and make it more easy-to-use and reduce cost without compromising the analytical performance such as sensitivity and specificity, as well as at a greater scale than heretofore possible.
Keywords: biosensor; environmental analysis; agricultural analysis; food safety; health; 31 Biological Sciences; 32 Biomedical and Clinical Sciences; 3106 Industrial Biotechnology; 40 Engineering; 4003 Biomedical Engineering; 3206 Medical Biotechnology; agricultural analysis